Functional Analysis of Unilateral Cleft-Lip Palate and Skeletal Class III Individuals - M. Okan Akçam; Erhan Özdiler; Tunç Altıok; Birol Özel; Ensar Başpınar (Turkish Journal of Orthodontics, 1999)

(untitled)
The aim of the current study was to determine and compare mandibular functions of cleft lip and palate (CLP) patients and Angle Class III individuals by using modified ‘Rakosi Functional Analysis’ method. Randomly selected 14 unilateral CLP patients with a mean age of 12.5±2.2 years and 33 skeletal Class III orthodontic patients with a mean age of 13.1±4.3 years were the subjects of our study. All subjects were evaluated clinically by modified ‘Rakosi Functional Analysis’, in accordance with scoring the findings. Descriptive and non-parametric tests (Mann-Whitney U) were applied to the scores of Rakosi analysis for evaluating differences between the CLP and Class III groups. According to statistical analysis, significant differences was observed in the total intracapsular parameters (P≤0,05) and in the overall score of all parameters (P≤0,01) between the two groups. Descriptive values showed that mean scores of the CLP group was greater than the Class III group. As a result, it may be suggested that temporomandibular joint dysfunction risk is higher in unilateral CLP when compared to Class III individuals. These findings do not explain the causes of the differences between the two groups leading us to conclude that further studies required on occlusal differences and muscle function by means of more improved and invasive methods.